Atalantiaphyllines A-G, prenylated acridones from Atalantia monophylla DC. and their aromatase inhibition and cytotoxic activities. (December 2020) - Pailee, Phanruethai; Prawat, Hunsa; Ploypradith, Poonsakdi; Mahidol, Chulabhorn; Ruchirawat, Somsak; Prachyawarakorn, Vilailak
Abstract: Seven previously undescribed acridones, named atalantiaphyllines A-G, along with twenty-six known compounds were isolated from the dichloromethane extracts of roots and stems of Atalantia monophylla DC. Their structures were elucidated by analysis of extensive NMR and HRMS data. Aromatase inhibition, cytotoxicity against MOLT-3, HepG2, A549 and HuCCA-1 cell lines and DPPH radical scavenging activity of these compounds were evaluated. Most of the tested acridones exhibited higher potency in inhibiting aromatase than the positive control, ketoconazole, with IC50 values in the range of 0.08–2.0 μM. In the cytotoxicity assay, cycloataphylline A, N -methylbuxifoliadine E and atalantiaphylline G were selectively cytotoxic against MOLT-3 cell line with IC50 values of 8.0, 5.4 and 9.8 μM, respectively, while only atalaphyllidine exhibited highest antioxidant activity as evaluated by DPPH free radical scavenging assay with an IC50 value of 22.4 μM. Graphical abstract: Image 1 Highlights: Seven undescribed atalantiaphyllines isolated from Atalantia monophylla . Most isolated acridones exhibited higher aromatase inhibition than ketoconazole. Some acridone showed the high DPPH radical scavenging activity.